(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to evaluate the microbiological safety of chicken meat marketed in Al-Bayda City, Libya, by analyzing samples of both locally produced and imported chicken for the presence of Escherichia coli ( E. coli ) and determining the total viable count (TVC). The results indicated that all samples were within the permissible limits according to international standards, confirming the overall microbiological safety of the meat. However, higher contamination levels were observed in locally produced chicken compared to imported samples. For imported chicken, the mean TVC values were 2.7 log CFU/g in breast meat and 3.6 log CFU/g in thigh meat, while E. coli counts ranged from 1.8 log CFU/g in breast to 2.3 log CFU/g in thigh samples, all within internationally accepted limits (6–7 log CFU/g for TVC and <3–4 log CFU/g for E. coli , according to WHO/FAO/EFSA). In locally produced chicken, the mean TVC reached 6.28 log CFU/g in both breast and thigh samples, whereas the mean E. coli count was 3.01 log CFU/g. Although these values did not exceed the maximum permissible limits, they approached the upper thresholds, reflecting a higher contamination level that could pose a potential risk under poor storage or handling conditions. Based on these findings, the study recommends strengthening sanitary control measures, improving hygiene practices and cold-chain management in the local poultry production sector, and raising consumer awareness about proper cooking practices as an effective measure to reduce potential microbiological risks.